Exosomes: A Friend or Foe for Osteoporotic Fracture? - Yang, Zhimin; Zhang, Wenchao; Ren, Xiaolei; Tu, Chao; Li, Zhihong (Frontiers in Endocrinology, 2021)
The clinical need for effective osteoporotic fracture therapy and prevention remains urgent. The occurrence and healing of osteoporotic fracture are closely associated with the continuous processes of bone modeling, remodeling, and regeneration. Accumulating evidence has indicated a prominent role of exosomes in mediating multiple pathophysiological processes, which are essential for information and materials exchange and exerting pleiotropic effects on neighboring or distant bone-related cells. Therefore, the exosomes are considered as important candidates both in the occurrence and healing of osteoporotic fracture by accelerating or suppressing related processes. In this review, we collectively focused on recent findings on the diagnostic and therapeutic applications of exosomes in osteoporotic fracture by regulating osteoblastogenesis, osteoclastogenesis, and angiogenesis, providing us with novel therapeutic strategies for osteoporotic fracture in clinical practice.